Measuring transit-oriented development (TOD) network complementarity based on TOD node typology - Grigolon, A. (2020)
In this paper, a TOD typology was developed based on built-form indicators to identify the roles different types of nodes play within the transit network and to discuss complementarity effects between TOD nodes within the TOD network. The study area is the Arnhem-Nijmegen city region in the Netherlands, which has a TOD network of 22 train stations. The results illustrated that differentiation among the TOD nodes in terms of residential housing prices and building uses contributed to a more diversified offer in terms of activities and functions of the TOD region and indicates complementarity between stations. Thus, TOD should be assessed and planned in a network system perspective, with the understanding that the nodes are pieces that contribute to the performance of the network.